Effect of different dietary protein level on growth, production and survivability of threatened Mystus cavasius (Hamilton-Buchanan 1822) in pond habitat - Samad, Md Abdus; Alice, Esmot Jahan; Pal, Dipankar (Asian Journal of Medical and Biological Research, 2021)
A study was undertaken to determine the effect of different dietary protein levels on growth, survival and production of Mystus cavasius (Hamilton-Buchanan 1822) with three experimental diets containing 29%, 32% and 35% protein level applied simultaneously to three treatments T1, T2 and T3 respectively each with three replications. The stocking density (1, 11, 150/ha), initial weight (3.00±00 g) and length (2.00±0.00 cm) of fish were same for all the treatments. No significant (P>0.05) difference was found for the mean values of water quality parameters. A suitable range of water quality parameters were recorded with the environment of experimental ponds. In terms of growth, production and survival, relatively highest performance was found in the treatment T3. After 180 days of rearing, average weight gain was 29.16±0.43 g, 31.17±0.30 g and 37.44±0.32 g with the above three different feeds, respectively. The average daily gain (ADG) and specific growth rate (SGR) of all treatments showed significant difference (P<0.05) and the highest value (0.21±0.04 and 1.43±0.01%) was found with the 35% dietary protein level containing diet. Feed conversion ratio (FCR) improved with increase of dietary protein. The findings of FCR were 2.97±0.02 at 29% protein level (T1), 2.64±0.02 at 32% protein level (T2) and 2.20±0.01 at 35% protein level (T3). The results of protein efficiency ratio (PER) values were fairly similar of 1.17±0.02 and 1.18±0.01 for 29% and 32% protein level containing diets respectively indicating low efficiency and the highest efficiency (1.30±0.01) was found with 35% protein level. The findings of condition factor in different treatments for Mystus cavasius were not significantly (P>0.05) varied with the treatments. Calculated values of condition factor were 1.04±0.00, 1.03±0.03 and 1.09±0.05 in treatment T1, T2 and treatment T3, respectively. In pond culture, the performance of treatment T3 was found to be better than the treatment T1 and T2. The production was of 3616±16.74 kg/ha in T3 during the culture period of six months. The best cost benefit ratio (CBR) value (1.98±0.02) was also found with treatment T3. The 35% dietary protein level with treatment T3 resulted in best growth performance and was probably adequate to meet the dietary protein needs of Mystus cavasius (Hamilton-Buchanan, 1822). Asian J. Med. Biol. Res. December 2020, 6(4): 659-673